2013
DOI: 10.3233/nre-130819
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the progressive walking-to-running technique on gait kinematics, ultrasound imaging, and motor function in spastic diplegic cerebral palsy – an experimenter-blind case study

Abstract: PURPOSE: The purpose of this study was to investigate the effects of the progressive walking-to-running technique (PWRT) in a child with spastic diplegic cerebral palsy (CP). DESIGN: A single case study with pre-/post-test. SUBJECT: An 11-year-old male, diagnosed with spastic diplegic CP. METHODS: The PWRT was provided for 60 minutes a day, 2 times a week for 12 weeks. Gross motor function tests, ultrasound imaging, hand-held dynamometer, and the Vicon motion capture system were used to determine motor functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 49 publications
0
14
0
2
Order By: Relevance
“…Consequently 57 articles were selected for full‐text review. Of these, 41 articles were deemed to meet the inclusion/exclusion criteria; reasons for exclusion of 16 articles are noted in Figure . One study population was reported in two articles; to avoid duplicates, results were reported as Provost et al .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Consequently 57 articles were selected for full‐text review. Of these, 41 articles were deemed to meet the inclusion/exclusion criteria; reasons for exclusion of 16 articles are noted in Figure . One study population was reported in two articles; to avoid duplicates, results were reported as Provost et al .…”
Section: Resultsmentioning
confidence: 99%
“…Training intensity varied from as little as 15 minutes gait training three times per week, up to 1‐hour sessions five times per week . One study was not clear about the training intensity provided …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations